Pendidikan Pembangunan Berkelanjutan Dimensi Pelestarian Lingkungan Melalui Model Pembelajaran RADEC Pada Pembelajaran IPA Di Sekolah Dasar - Hana Lestari; Ima Rahmawati (Institut Agama Islam Sahid (INAIS) Bogor, 2022)
This study aims to provide an overview of sustainable development education on the dimensions of environmental conservation through the RADEC model in science learning in elementary schools (SD). This study used a descriptive qualitative approach involving 4 teachers and 20 elementary school students in the city of Bogor which was taken based on the purposive sampling technique. Data were collected through interviews, observations, and elementary science curriculum documents, which were processed using triangulation techniques. The results of this study indicate that (1) in general the indicators derived from basic competencies can be oriented towards the goal of sustainable education on the dimensions of environmental conservation; (2) Science learning packaged in thematic learning at the elementary school level can provide opportunities in the process of implementing sustainable development education holistically and comprehensively; (3) The RADEC model can stimulate students to learn actively, not only mastering the concept of environmental conservation but also thinking skills and attitudes in preserving the environment; (4) The RADEC model can be applied in synchronous and asynchronous online learning so that it is suitable for use during the Covid 19 pandemic